2020
DOI: 10.1101/2020.01.27.920843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous stimulation of RuBP regeneration and electron transport increases productivity and water use efficiency under field conditions

Abstract: One sentence summary: Simultaneous stimulation of RuBP regeneration and electron transport results in improvements in biomass yield in glasshouse and field grown tobacco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Apart from their protective role, carotenoids also act as key regulatory molecules in both photosynthetic and non-photosynthetic organisms (Blankenship 2010). For example, carotenoids are cleaved by enzymes such as CCDs (carotenoid cleavage dioxygenases) and NCED's (9-cis-epoxy carotenoid dioxygenases) and the products act as precursors for the generation of vital primary and secondary metabolites, including the phytohormones abscisic acid (Parry et al 1990;Qin and Zeevaart 1999;Tan et al 2003;Simkin 2021) and strigolactones (Booker et al 2004;Lopez-Obando et al 2015;Schwartz et al 2004;Snowden et al 2005;Vogel et al 2010) as well as important flavours and aroma compounds, in fruit pericarp, flowers and seeds (Auldridge et al 2006a(Auldridge et al , 2006bGiberti et al 2019;Rubio et al 2008;Schwartz et al 2001;Simkin et al 2010Simkin et al , 2004cSimkin et al , 2004b. These carotenoidderived flavour and aroma compounds are valuable products in foods, flowers (Lin et al 2002;Mahattanatawee et al 2005), wine (Winterhalter and Gök 2013), Kentucky bourbon (Poisson and Schieberle 2008), cosmetic and spice industries (Bouvier et al 2003a(Bouvier et al , 2003b.…”
Section: Role Of Carotenoids In Light Harvesting and Photoprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from their protective role, carotenoids also act as key regulatory molecules in both photosynthetic and non-photosynthetic organisms (Blankenship 2010). For example, carotenoids are cleaved by enzymes such as CCDs (carotenoid cleavage dioxygenases) and NCED's (9-cis-epoxy carotenoid dioxygenases) and the products act as precursors for the generation of vital primary and secondary metabolites, including the phytohormones abscisic acid (Parry et al 1990;Qin and Zeevaart 1999;Tan et al 2003;Simkin 2021) and strigolactones (Booker et al 2004;Lopez-Obando et al 2015;Schwartz et al 2004;Snowden et al 2005;Vogel et al 2010) as well as important flavours and aroma compounds, in fruit pericarp, flowers and seeds (Auldridge et al 2006a(Auldridge et al , 2006bGiberti et al 2019;Rubio et al 2008;Schwartz et al 2001;Simkin et al 2010Simkin et al , 2004cSimkin et al , 2004b. These carotenoidderived flavour and aroma compounds are valuable products in foods, flowers (Lin et al 2002;Mahattanatawee et al 2005), wine (Winterhalter and Gök 2013), Kentucky bourbon (Poisson and Schieberle 2008), cosmetic and spice industries (Bouvier et al 2003a(Bouvier et al , 2003b.…”
Section: Role Of Carotenoids In Light Harvesting and Photoprotectionmentioning
confidence: 99%
“…Several studies have reported that enhanced photosynthetic capacity can be achieved in leaves by increasing photosynthetic electron transport rates (Chida et al 2007;Lopez-Calcagno et al 2020;Simkin et al 2017b;Yadav et al 2018), manipulating Calvin Benson Cycle (CBC) enzymes to increase energy conversion (Driever et al 2017;Lefebvre et al 2005;Lopez-Calcagno et al 2020;Simkin et al 2015Simkin et al , 2017aSimkin et al , 2019Raines et al 2022), modifying photorespiration (López-Calcagno et al 2018;Simkin et al 2017a;Timm et al 2012), along with improving the kinetics of non-photochemical quenching (NPQ), a photoprotective mechanism employed by plants under high light stress, and the re-allocation of absorbed energy back into photosynthesis rather than being dissipated as heat (Glowacka et al 2018;Kromdijk et al 2016). Furthermore, recent studies have also suggested that increasing the photosynthetic capacity of non-foliar tissue such as fruits, stems and wheat ears could play a key role in improving yield (Simkin et al 2020).…”
Section: Introductionmentioning
confidence: 99%